Night at the museum - Levy, Shawn, 1968-; Columbus, Chris; Barnathan, Michael; Garant, Robert Ben, 1970-; Lennon, Thomas, 1970-; Stiller, Ben, 1965-; Gugino, Carla, 1971-; Van Dyke, Dick; Rooney, Mickey; Cobbs, Bill; Cherry, Jake, 1996-; Gervais, Ricky; et al. (Beverly Hills, Calif. 20th Century Fox Home Entertainment, 2007)
Larry Daley is a divorced father who can't seem to keep a job for more than a week. As a last resort, Larry applies for a job as a night shift security guard at the American Museum of Natural History. However, a seemingly easy job turns out to be an adventure when he finds that an ancient curse causes the "inhabitants" of the museum to come to life at night.
Originally released as a motion picture in 2006.
Based upon the book by Milan Trenc.
Full screen 1.33:1.
Special features: Commentary by director Shawn Levy; commentary by writers Robert Ben Garant and Thomas Lennon.
Director of photography, Guillermo Navarro ; editor, Don Zimmerman ; music, Alan Silvestri ; costume designer, Renee April ; production designer, Claude Pare ; visual effects supervisor, Jim Rygiel.
Ben Stiller, Carla Gugino, Dick Van Dyke, Mickey Rooney, Bill Cobbs, Jake Cherry, Ricky Gervais, Robin Williams.
Keywords: Trenc, Milan -- Film adaptations; American Museum of Natural History -- Drama; Police, Private -- New York (State) -- New York -- Drama; Divorced fathers -- New York (State) -- New York -- Drama; Museum exhibits -- New York (State) -- New York -- Drama; Fathers and sons -- New York (State) -- New York -- Drama; New York (N.Y.) -- Drama; Comedy -- Feature; Film adaptations; Video recordings for the hearing impaired; Drama; Feature films